CHARACTERIZATION OF THE CHARACTER IN DEMON SLAYER MANGA (KIMETSU NO YAIBA) BY KOYOHARU GOTOUGE - Zahra Fadhilah Raihani Mantau; Christo R.Pua; Mariam L. M. Pandean (Universitas Sam Ratulangi, 2025)
The focus of this research refers to the characteristization of the character in the comic or manga Demon Slayer (Kimetsu No Yaiba) by Koyoharu Gotouge. The theory of this study is about character characteristics from Burhan Nurgiantoro and Edgar Roberts. The research method used in this research is a qualitative descriptive method. Based on the results of the research, the author identified eight characters who played an important role in the development of the Demon Slayer manga story, namely Tanjiro Kamado (main character, protagonist, complex, developing, neutral), Nezuko Kamado (main character, protagonist, static, neutral), Sakonji Urokodaki (minor character, protagonist, simple, static, typical), Muzan Kibutsuji (main character, antagonist, simple, static, typical), Giyu Tomioka (supporting character, protagonist, simple, static, typical), Tamayo (minor character, protagonist, simple, static, typical), Yushiro(minor character, protagonist, simple, static, typical) and Zenitsu Agatsuma (supporting character, protagonist, complex, typical);2) furthermore, each character has its own characteristics.